2020
DOI: 10.1042/bsr20194404
|View full text |Cite
|
Sign up to set email alerts
|

MEHP interferes with mitochondrial functions and homeostasis in skeletal muscle cells

Abstract: Di (2-ethylhexyl) phthalate (DEHP) is a plasticizer frequently leached out from polyvinyl chloride (PVC) products and is quickly metabolized to its monoester equivalent mono(2-ethylhexyl) phthalate (MEHP) once enters organisms. Exposure to DEHP/MEHP through food chain intake has been shown to modified metabolism but its effect on the development of metabolic myopathy of skeletal muscle (SKM) has not been revealed so far. Here, we found that MEHP repressed myogenic terminal differentiation of proliferating myob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 39 publications
(25 reference statements)
0
9
0
Order By: Relevance
“…For instance, DEHP exposure is associated with an elevation in cellular oxidative stress, 68 which is linked to a subsequent increase in carbon intermediates. 27, 69 DEHP may also contribute to mitochondrial dysfunction, 70, 71 which diminishes cellular energy supply and increases the utilization of non-oxidative energy metabolism pathways. Alternatively, a DEHP-induced elevation of non-oxidative metabolites could be due to a high glycolytic rate that strains the oxidative capacity of the mitochondria 72 ; however, there is inconsistent evidence of hyperactive glycolysis after DEHP exposure.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, DEHP exposure is associated with an elevation in cellular oxidative stress, 68 which is linked to a subsequent increase in carbon intermediates. 27, 69 DEHP may also contribute to mitochondrial dysfunction, 70, 71 which diminishes cellular energy supply and increases the utilization of non-oxidative energy metabolism pathways. Alternatively, a DEHP-induced elevation of non-oxidative metabolites could be due to a high glycolytic rate that strains the oxidative capacity of the mitochondria 72 ; however, there is inconsistent evidence of hyperactive glycolysis after DEHP exposure.…”
Section: Discussionmentioning
confidence: 99%
“…Although the addition of plasticizers to PLA is an accepted method to improve its mechanical properties, plasticizers are prone to migration and leaching out of the blend as they are not covalently bound to the polymer backbone . This compromises the integrity of the product and can lead to widespread environmental contamination and potential human exposure. , Consequently, the investigation of plasticizer accumulation in the environment as well as the health effects of plasticizer exposure on both humans , and animals remains an area of active research. To date, there have been numerous plasticizers developed for the production of flexible PLA including but not limited to citrate esters, polyethylene glycol analogues, levulinic acids, tartaric acids, malic acids, and functionalized epoxidized soybean oils .…”
Section: Introductionmentioning
confidence: 99%
“…Impairment of the oxidative phosphorylation was previously described on skeletal muscle cells exposed to MEHP; the authors reported a degradation of complex I, which was triggered by ROS production [ 56 ]. In the present study, the redox imbalance was found subsequently to the mitochondrial respiration alteration, but it is not excluded that early mitochondrial ROS production occurs.…”
Section: Discussionmentioning
confidence: 99%